Melody and the sea dragon - Kit, Katy (Mermaid mysteries ;, 2012)
Coral, Jasmine, Rosa, and Sula help recover a missing chest of jewels, and Melody appeals to King Nepture on behalf of the falsely accused and banished sea dragon, in time for all to enjoy the spring festivities.